2019
DOI: 10.1101/821603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dual Histone Methyl Reader ZCWPW1 Facilitates Repair of Meiotic Double Strand Breaks

Abstract: Meiotic crossovers result from homology-directed repair of double strand breaks (DSBs). Unlike yeast and plants, where DSBs are generated near gene promoters, in many vertebrates, DSBs are enriched at hotspots determined by the DNA binding activity of the rapidly evolving zinc finger array of PRDM9 (PR domain zinc finger protein 9). PRDM9 subsequently catalyzes trimethylation of lysine 4 and lysine 36 of Histone H3 in nearby nucleosomes. Here, we identify the dual histone methylation reader ZCWPW1, which is ti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
2
3
0
Order By: Relevance
“…Immunofluorescence images in this study revealed that Zcwpw1 functioned in DNA repair and synapsis. Very recently, Zcwpw1 was identified as a histone H3K4me3 reader required for the repair of PR domain zinc finger protein 9-dependent DNA DSBs and synapsis by three independent research groups ( 49 , 50 , 51 , 52 ), which was consistent with our observations. Tesmin and 1700102P08Rik have also recently been identified as essential genes in spermatogenesis ( 53 , 54 ), yet their mechanisms of involvement in meiosis-essential biological events still require further exploration.…”
Section: Discussionsupporting
confidence: 92%
“…Immunofluorescence images in this study revealed that Zcwpw1 functioned in DNA repair and synapsis. Very recently, Zcwpw1 was identified as a histone H3K4me3 reader required for the repair of PR domain zinc finger protein 9-dependent DNA DSBs and synapsis by three independent research groups ( 49 , 50 , 51 , 52 ), which was consistent with our observations. Tesmin and 1700102P08Rik have also recently been identified as essential genes in spermatogenesis ( 53 , 54 ), yet their mechanisms of involvement in meiosis-essential biological events still require further exploration.…”
Section: Discussionsupporting
confidence: 92%
“…Immunofluorescence images in this study divulged that Zcwpw1 played a role of DNA repair and synapsis. Recently, Zcwpw1 was identified as a histone H3K4me3 reader required for synapsis and repair of PRDM9-dependent DSBs by other three research groups [37][38][39][40] , which was consistent with our observations. Whereas, knockout of the other two genes, Tesmin and 1700102P08Rik, were found have no effect on DNA repair and synapsis, indicating they could be involved in presently unknown molecular events inspected by midPachytene checkpoint.…”
Section: Dissucssionsupporting
confidence: 92%
“…However, an increased lifespan of resected DSBs is not always associated with the removal of SPO11-RI. For example, loss of ZCWPW1, a dual histone methylation reader of PRDM9, does not impact DSB placement or SPO11-RI formation 48 . Zcwpw1 -/spermatocytes display decreased DSB repair and asynapsis phenocopying loss of PRDM9 48 ; however, SPO11-RI is present at WT levels in Zcwpw1 -/spermatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, loss of ZCWPW1, a dual histone methylation reader of PRDM9, does not impact DSB placement or SPO11-RI formation 48 . Zcwpw1 -/spermatocytes display decreased DSB repair and asynapsis phenocopying loss of PRDM9 48 ; however, SPO11-RI is present at WT levels in Zcwpw1 -/spermatocytes. Thus, failure in synapsis and DSB repair does not necessarily lead to an increased fraction of breaks that are fully and symmetrically processed by MRE11.…”
Section: Discussionmentioning
confidence: 99%